PERBANDINGAN HUKUM DAGANG KONVENSIONAL DAN SYARIAH PADA TRANSAKSI DIGITAL INDONESIA - Nursania Nursania; Lisa Arniati Rambe; Ahmad Khaidir Assyukri; Asmarina (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
The rapid development of digital commerce in Indonesia has significantly transformed traditional trading systems into more efficient electronic-based transactions. This study aims to analyze and compare conventional commercial law and Islamic commercial law in regulating digital trade transactions. The research uses a qualitative approach with a library research method by examining relevant literature, legal documents, and academic sources. The findings show that conventional commercial law emphasizes legal certainty and contractual validity based on formal agreements, while Islamic commercial law integrates ethical and moral values such as justice, transparency, and the prohibition of riba, gharar, and maisir. Both legal systems share similarities in recognizing mutual consent and clarity of transactions, but differ in their foundational principles. The integration of both systems is considered important in creating a fair, transparent, and sustainable digital trading ecosystem in Indonesia. These findings highlight the importance of harmonizing legal certainty and ethical values in modern digital transactions.